Sosialiasi Cerdas Menghadapi Disinformasi di Era AI dan Media Sosial: Program Pengabdian Masyarakat di Desa Jaharun, Kecamatan Galang Kabupaten Deli Serdang - Siti Maysarah; Revina Maulida; Astri Wulandari; Hilmi Atha Syafiq; Cindy Mei Yana Munthe; Sintia Dwi Anggring (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of information and communication technology has transformed the way people access information, interact, and live their daily lives. In this regard, students from the Mathematics Education Study Program at the State Islamic University of North Sumatra conducted